USING FISHBONE TECHNIQUE TO IMPROVE READING SKILL OF NARRATIVE TEXT IN THE TENTH GRADERS OF SMA N 1 GRABAG IN THE SCHOOL YEAR 2017/2018 - Niken Utari (Faculty of Education and Teachers Training, 2018)
Reading is one of the four language skills of English that is difficult for most of students. This problem is also faced by tenth graders of SMA N 1 Grabag. The result of the average of score of the reading test is 44.8, it is less than the standard minimum which is 67. There are several factors which influence students’ low reading skill, some of them are the students’ low motivation in learning English and they feel bored to the teacher’s teaching technique. The writer conducted the research to overcome that problem by applying Fishbone Technique. There are two objectives of this study; the first is to describe the increase of learning motivation in reading narrative text of the tenth graders who are taught using Fishbone technique. The second is to explain the improvement of narrative text reading skill of the tenth graders who are taught using Fishbone technique. This is a classroom action research. The subjects of the study were 26 students of X IPS 4 of SMA N 1 Grabag in the school year 2017/2018. It was divided into Pre-Cycle, Cycle I, and Cycle II. The writer used test, questionnaire, documentation, and observation to collect the data. The data were analyzed using qualitative and quantitative data analysis technique. The result of the observation and questionnaire show that there are improvement of the students’ motivation after the writer taught the students using Fishbone technique in narrative text reading skill. It was proved by the change of students’ behavior from Pre-Cycle to Cycle II. In Pre-Cycle, the test result was 44.8, in Cycle I is 83.26, and in Cycle II is 87.69. The result of this research shows that the students’ reading skill in narrative text improves in each cycle after they are taught using Fishbone technique. Based on the result above, the writer recommends the teacher to apply Fishbone Technique as an alternative way of teaching reading narrative text.